Assessment of Bearing Capacity and Settlement Characteristics of Organic Soil Reinforced by Dune Sand and Sodium Silicate Columns: A Numerical Study (Journal of Engineering, 2024)
Organic soil is problematic soils in geotechnical engineering due to its properties, as it is characterized by high compressibility and low bearing capacity. Therefore, several geotechnical techniques tried to stabilize and improve this soil type. In this study, sodium silicate was used to stabilize sand dune columns. The best sodium silicate concentration (9%) was used, and the stabilized sand dune columns were cured for seven days. The results for this soil were extracted using a numerical analysis program (Plaxis 3D, 2020).In the case of studying the effect of (L/D) (where ‘’L” and ‘’D’’ length and diameter of sand dune columns) of a single column of sand dunes stabilized with sodium silicate with a different diameter, the results showed that the best effect was for L/D of (4) with D equal to (0.7m) in the end bearing columns type. In the case of studying a group of columns, the percentage of improvement in soil bearing ratio increased with increasing the number of columns in both floating and end bearing types. When using (8-columns) with a square distribution pattern, the optimum improvement was at the end bearing and at the ratio L/D of (6), where the improvement percentage was (666%) compared to the unimproved soil.